Advances in Networks and Communications First International Conference on Computer Science and Information Technology, CCSIT 2011, Bangalore, India, January 2-4, 2011. Proceedings, Part II - Meghanathan, Natarajan; Kaushik, Brajesh Kumar; Nagamalai, Dhinaharan (Springer eBooks., 2011)
This volume constitutes the second of three parts of the refereed proceedings of the First International Conference on Computer Science and Information Technology, CCSIT 2010, held in Bangalore, India, in January 2011. The 66 revised full papers presented in this volume were carefully reviewed and selected. The papers are organized in topical sections on networks and communications; network and communications security; wireless and mobile networks.